DIFFERENCES IN PARAMETERS OF BONE MINERAL DENSITY BETWEEN ELITE ATHLETES AND NON ATHLETES - Anita Šolaja; Milan Šolaja; Borislav Obradović (Exercise and Quality of Life, 2014)
The aim of this study is to investigate the differences in parameters of bone mineraldensity in elite track and field athletes and sedentary male controls, respectively non-athletes.The research included 15 athletes who are members of the national junior track and field teamof Serbia and 15 non-athlete boys, aged 17 to 19 years. Sahara (Hologic, Inc., MA 02154,USA) clinical sonometer was used for assessing bone density. The parameters of bonemineral density were measured, Speed of sound (SOS), Broadband ultrasound attenuation(BUA), Bone mineral density (BMD) and Width of the heel bone, as well. T-test for twoindependent groups confirmed that there is statistically significant difference between elitetrack and field athletes and non-athletes in all measured parameters (p < 0.05). The results ofthis study confirm the significant effects of practicing track and field events on increasingbone mineral density and preventing osteoporosis.